Training of food handlers in the fast-food sector and learning assessment using the Plickers methodology (Research, Society and Development, 2024)
The objective of this study was to train food handlers in the fast food segment and evaluate their learning using the Plickers methodology. This is a quantitative, exploratory, descriptive and interventional scientific research that integrates a bibliographic review on the training of food handlers in fast food restaurants in the city of Piraí-RJ. For the training of food handlers, dynamics on simple and practical GMP were applied. The Plicklers methodology was applied to evaluate the consolidation of these handlers' knowledge on Good Manufacturing Practices (GMP). It was found that the majority of food handlers are female, 72% (n=8). Before the training, employees were assessed on their understanding of GMP, where it can be observed that 90% (n=10) of food handlers correctly know about the practices not allowed in production sites. However, 81% (n=9) did not know how to answer what should be done when they have a wound on their hands. It was observed that even after training using the Plickers methodology, handlers had doubts about the correct way to sanitize their hands, with 37% (n=4) unable to answer correctly. It was concluded that, after training, there was an improvement in understanding about safe food handling, although there are still gaps, especially in relation to hand hygiene. Therefore, it is necessary to implement continuous training and dynamics to address these issues.